Analisis Penggunaan E-Commerce terhadap Bisnis Usaha Mikro, Kecil, dan Menengah (UMKM) - Belqis Putri Himmatul Karimah; Diah Priharsari; Tibyani Tibyani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
E-commerce has recently been favored by both large and small businesses. This is because promotion through online media or digital marketing is easier to reach consumers in terms of introducing or selling their products so it is very helpful for business people. This study aims to determine the impact of using e-commerce on SMEs. Data collection for this study was carried out using a semi-structured interview method to MSME business actors who have used e-commerce to sell their products. From the interview data that has been carried out, then analyzed using the thematic analysis method, which is a method of analyzing data to identify patterns and find topics based on data collected by researchers (Braun and Clarke, 2006). The result is that several categories explain how MSMEs use e-commerce, namely individual features or individual abilities, reasons for not using other e-commerce than those currently used, several obstacles such as infrastructure, technology, promotion, and unpleasant experiences that experienced by MSME business actors when using e-commerce.